PENGUATAN LITERASI DIGITAL DAN OPTIMALISASI DIGITAL MARKETING PENGUSAHA SABLON DI DESA CIKASUNGKA, SOLEAR, TANGERANG - Komalasari, Nia; Nurhafsari, Asri (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This community service aims to provide knowledge regarding digital literacy so that the public can use information technology wisely and responsibly, avoiding being easily influenced by inaccurate news, and protecting themselves from illegal online loan offers. Furthermore, this activity aims to provide additional knowledge and implement digital marketing practices through WhatsApp and TikTok to market screen printing products. By implementing digital marketing, marketing reach will expand, increasing the opportunity for consumers to purchase screen printing products. The method includes focus group discussions (FGDs), outreach, and practical exercises. This activity progresses through preparation, implementation, and evaluation stages. The results of this community service are that participants have a greater understanding and appreciation of the importance of digital literacy to protect the public from the negative impacts of current digital technology. Participants also understand the importance of online loan services (pinjol), emphasizing the need to be vigilant, selective, and not easily tempted by illegal loan offers. Meanwhile, regarding digital marketing, participants expressed enthusiasm for trying digital marketing through WhatsApp and TikTok. Participants are able to manage their stores using WhatsApp Business or their TikTok stores to promote and market their screen-printing entrepreneurs